2007
DOI: 10.1371/journal.pone.0000478
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Core Kinetochore Composition and Assembly in Drosophila melanogaster

Abstract: BackgroundKinetochores are large multiprotein complexes indispensable for proper chromosome segregation. Although Drosophila is a classical model organism for studies of chromosome segregation, little is known about the organization of its kinetochores.Methodology/Principal FindingsWe employed bioinformatics, proteomics and cell biology methods to identify and analyze the interaction network of Drosophila kinetochore proteins. We have shown that three Drosophila proteins highly diverged from human and yeast Nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
189
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(212 citation statements)
references
References 54 publications
21
189
2
Order By: Relevance
“…However, with the exception of CENP-C, no counterparts to the CCAN have been found to date in Drosophila, which has monocentric chromosomes. The reported dependency of Ndc80 complex localization on the KNL1 ortholog in Drosophila (Przewloka et al, 2007) suggests that, as in C. elegans, the CCAN protein group may have been lost in this lineage, further work is needed to test if this indeed the case.…”
Section: M Cheeseman Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…However, with the exception of CENP-C, no counterparts to the CCAN have been found to date in Drosophila, which has monocentric chromosomes. The reported dependency of Ndc80 complex localization on the KNL1 ortholog in Drosophila (Przewloka et al, 2007) suggests that, as in C. elegans, the CCAN protein group may have been lost in this lineage, further work is needed to test if this indeed the case.…”
Section: M Cheeseman Et Almentioning
confidence: 99%
“…A key player in kinetochore assembly in C. elegans is KNL-1, which functions downstream of the inner kinetochore components such as CENP-A, but upstream of all known outer kinetochore proteins (Desai et al, 2003;Cheeseman et al, 2004). KNL-1 belongs to a conserved protein family that includes budding yeast Spc105 (Nekrasov et al, 2003), fission yeast Spc7 (Kerres et al, 2004), Drosophila Spc105R (Przewloka et al, 2007), and a novel protein previously identified in human cells known as AF15q14, D40, CASC5, or Blinkin (Cheeseman et al, 2004;Obuse et al, 2004;Kiyomitsu et al, 2007). AF15q14 is present in all vertebrates including chicken (Gallus gallus).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D. melanogaster provides a well-studied example illustrating the evolutionary plasticity of centromere and kinetochore organization. All 16 centromere proteins of the so-called CCAN (constitutive centromere associated network) with the exception of Cenp-C are absent in the fly (Heeger et al 2005;Przewloka et al 2007;Schittenhelm et al 2007;Westermann and Schleiffer 2013). Cenp-C, which binds directly to Cenp-A/Cid, recruits the kinetochore proteins of the KMN network composed of Knl-1/Spc105 and the heterotetrameric Mis12-and Ndc80-complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Drosophila Mis12 complex lacks the Dsn1 subunit present in yeast and 5 vertebrates (Przewloka and Glover 2009;Przewloka et al 2007;Schittenhelm et al 2007). …”
Section: Introductionmentioning
confidence: 99%